BEHÇET'S DISEASE: CONCURRENT SKIN AND COLONIC BIOPSIES CAN BE DIAGNOSTIC. A CASE REPORT. (February 2015) - Vagaja, Nina; Parry, Jeremy; McCallum, Dugald
Abstract : Aim: Behçet's disease (BD), a rare systemic vasculitis, classically presents as oral, gastrointestinal and genital ulceration, uveitis and rash. However, BD's systemic nature may produce variable phenotypes and mimic other diseases. We present a diagnostically challenging case of BD, with focus on dermatopathological features that may aid diagnosis of BD in such cases. Methods: A 27-year-old male with one year's diagnosis of Crohn disease, established endoscopically during a year-long stay in Japan, presented with oral ulcers, gastrointestinal symptoms and erythema nodosum-like rash on the legs, forearms and face, requiring skin and colonoscopic biopsies. Results: Skin biopsies showed septal panniculitis with abundant infiltrating neutrophils, prominent multinucleation of giant cells and predominantly mononuclear venulitis. One antecubital lesion at cannulation site demonstrated pyoderma gangrenosum-like punched-out ulcer with undermining neutrophilic infiltrate, reflecting pathergy. Colonoscopy demonstrated oval crateroid colonic ulcers; biopsy showed superficial ulcerations without features of classical inflammatory bowel disease. Jointly, these findings were diagnostic of BD. Conclusion: BD is a multisystem disorder with pathologically non-specific features including abundance of neutrophils and variable vasculitic component. Examination of specimens from multiple sites, including evidence of cutaneous pathergy, can lead to a greater level of diagnostic confidence.